Performance of stocker steers grazing smooth bromegrass at two stocking rates and dewormed with morantel tartrate - Coffey, K.P.; Moyer, Joseph L.; Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Early-intensive grazing of smooth bromegrass reduced animal gains but improved gain/acre. Morantel tartrate reduced fecal nematode egg counts but had no effect on animal performance at either stocking rate
Keywords: Beef; Performance; Stocker steers; Bromegrass; Morantel tartrate; stocking rates